Meat Physical Characteristic of Sentul Kampung Kedu Crossing (Skkedu) - Harini Nurcahya; Sri Darwati; Nur Widayanti (Universitas Nasional Jakarta, 2022)
Sentul and kampung chicken are known as dual-purpose chicken, and kedu chicken is as laying hens. The crossing of sentul, kampung and kedu chicken produced SKKedu chicken. The crossing is expected to be produced local chickens that have superior meat quality from the combination of the three types of chicken. This study aimed to analyze the physical quality of SKKedu chicken meat. Tests were carried out on the flesh of the chest, upper thighs and lower thighs of 12 SKKedu chickens aged 12 weeks. Analysis of the meat physical characteristics included 4 variables pH value, cooking shrinkage, tenderness, and percentage of water binding power. The pH value of SKKedu meat in the upper thighs and lower thighs were the same (P> 0.05), while the breast meat was significantly different (P <0.05). The tenderness is only done on breast meat and obtained a value of 2.86 ± 0.50 kg cm-2. The different parts of meat did not have a significant effect (P> 0.05) on cooking losses of SKKedu chicken meat. Power binding to water (DMA) of breast and lower thigh meat was different (P <0.05) with the best DMA in the lower thighs. SKKedu chicken meat was still quite tender.